2012
DOI: 10.3354/esr00421
|View full text |Cite
|
Sign up to set email alerts
|

Satellite tracking of hawksbill turtles Eretmochelys imbricata nesting in northern Bahia, Brazil: turtle movements and foraging destinations

Abstract: Data on hawksbill Eretmochelys imbricata migratory patterns are virtually unknown for nesting populations in the South Atlantic Ocean. The most significant nesting ground for hawksbills in the South Atlantic is located in Brazil, specifically in the northern state of Bahia. From February to March 2005, 15 adult female hawksbills were equipped with satellite transmitters on beaches of northern Bahia. During the internesting period, satellite-tracked hawksbills remained in the coastal waters of northern Bahia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
6
44
1
3
Order By: Relevance
“…Core activity areas occurred in shallow waters (< 200 m) and were associated with coral reefs. Our results support previously described hawksbill internesting spatial behaviour observed in other internesting areas throughout the Caribbean (van Dam et al 2008, Marcovaldi et al 2012, Walcott et al 2012). Although we did not record diving depth, it appears turtles were likely to have been making shallow dives; indeed, hawksbill turtles probably exhibit shallow diving behaviour throughout the year (Storch et al 2005, Blumenthal et al 2009).…”
Section: Internesting Behavioursupporting
confidence: 93%
See 1 more Smart Citation
“…Core activity areas occurred in shallow waters (< 200 m) and were associated with coral reefs. Our results support previously described hawksbill internesting spatial behaviour observed in other internesting areas throughout the Caribbean (van Dam et al 2008, Marcovaldi et al 2012, Walcott et al 2012). Although we did not record diving depth, it appears turtles were likely to have been making shallow dives; indeed, hawksbill turtles probably exhibit shallow diving behaviour throughout the year (Storch et al 2005, Blumenthal et al 2009).…”
Section: Internesting Behavioursupporting
confidence: 93%
“…Numerous studies have suggested the key role of this species in maintaining the structure, ecology and evolution of coral reefs (León & Bjorndal 2002, Bjorndal & Jackson 2003. During the nesting season, which usually spans several months, females return repeatedly to the same beach to lay a variable number of clutches (Allen et al 2010, Marcovaldi et al 2012, Walcott et al 2012, Phillips et al 2013, similar to that documented for other marine turtle species. However, some populations of marine turtles remain within 100 m of the nesting beaches between nesting attempts (green turtles Chelonia mydas on Ascension Island; Hays et al 1999), while others may travel up to 100 km from the nesting beach to alternative sites (loggerhead turtles Caretta caretta in Greece; Schofield et al 2010).…”
Section: Introductionmentioning
confidence: 90%
“…The observation of hybrids introgressed with either parental species raises the possibility that hybrid individuals could display behavioural differences which could lead to divergent mating preferences, some tending to mate with E. imbricata and others with C. caretta . This behavioural difference was already observed among some of these hybrids found along the Brazilian coast where individuals exhibited different pattern of migrations in relation to either parental species (Marcovaldi et al. 2012, see details below).…”
Section: Discussionsupporting
confidence: 51%
“…Their internesting loops tend to be more like directional trajectories that can extend well offshore, typical of what might be expected for a pelagic drifter, and consequently are associated with much longer tracks and faster swimming speeds than those observed for loggerheads. Given these vast differences in behaviour and resulting internesting home ranges, loggerheads, and other hard-shell turtles (Maxwell et al, 2011;Blanco et al, 2013;Marcovaldi et al, 2012), are much easier to encompass in MPAs during this critical life history stage than are leatherbacks (Witt et al, 2008).…”
Section: Discussionmentioning
confidence: 99%